Makkau Sorong: Tradisi Uang Pelangkah Perkawinan di Lalampanua Kabupaten Majene Sulawesi Barat - Obed, Nurul Atika; Junaeda, St. (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2024)
This research aims to find out: why the Makkau Sorong tradition only applies to older sisters, the meaning of the Makkau Sorong tradition, preparation and implementation in the Makkau Sorong tradition in Lalampanua Village. This research uses descriptive research with qualitative data. The validity test was carried out using data triangulation techniques. The data analysis technique uses functional analysis. The results showed that: The Makkau Sorong tradition only applies to older sisters, because men are relatively active in choosing a mate, and women are passive, so if a younger sister's marriage precedes her older sister's, it is a pamali. This is a disgrace, the community will assume that the sister has something bad and not good in her, this is one of the reasons it is difficult for the sister to get a mate because it becomes a consideration in the future if there is a man who wants to propose to the sister. The meaning of the Makkau Sorong tradition as a condition for aborting pamali, as a form of request for blessing, apology, and a form of gratitude from the younger brother to the older brother who was preceded. Reparation and implementation in the Makkau Sorong tradition in Lalampanua Village